Multimodal Learning Practices in Psychology of Literature Courses in Higher Education - Firmansyah, Muhammad Bayu; Ridwan, M. (Universitas Muhammadiyah Malang, 2025)
The practice of teaching Literary Psychology in higher education often faces challenges due to the lack of pedagogical strategies capable of bridging the complexity of literary texts with the psychological dynamics embedded within them. Students frequently struggle to grasp the emotional and cognitive depth of narrative meaning because the dominant teaching approach remains monomodal. This study aims to explore students' perceptions of the application of multimodal learning in Literary Psychology courses and to examine the extent to which multimodal resources can promote the development of data, technology, and human literacy in the classroom. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation of the teaching and learning process, and documentation of student learning outcomes. The research subjects were students and faculty members from the literature program at one of Indonesia's state universities. The research findings indicate that the integration of multimodal resources—such as infographics, character analysis videos, and digital forums—significantly enhances active participation, psychological understanding of literary texts, and students' reflective sensitivity. Furthermore, these findings show that multimodal learning not only impacts material comprehension but also shapes an inclusive and transformative learning ecosystem. The conclusion of this study confirms that the multimodal approach is an adaptive and effective pedagogical strategy for developing the interpretive, critical, and literary abilities of literature students in the digital age.